ANALYSIS OF LOGIC MATHEMATICS INTELLIGENCE IN CLASS V SDN BANYUAJUH 4 ON BUILDING SPACE MATERIALS - Cahyani Setyatika Ramadhani; Evi Kharisma Azhari; Wahyu Kusuma Andini; Ananda Fitri Syarmila; Conny Dian Sumadi (Citra Dharma Cindekia, 2022)
Mathematical logic intelligence is intelligence that makes a person, quickly and accurately process numbers, think creatively, critically, and easily find solutions to every problem based on logical, systematic and rational thinking. The purpose of this study was to analyze the level of mathematical logic intelligence in the fifth grade students of SDN Banyuajuh 4 on the material of banging space. To analyze the level of students' mathematical logic intelligence, researchers observed student responses during learning, reviewed documentation, then correlated the results with information from various related references. The results of this study indicate that students do not show the characteristics of someone who has mathematical logic intelligence, for example students seem less interested in the material, students have not shown reason and creativity in solving math problems, and are less able to remember and use abstract symbols in mathematics. In addition, there is documentation of student learning outcomes on the material of building space which is also low. Therefore, it can be concluded that the level of mathematical logical intelligence of students in the class when viewed from the responses and student learning outcomes on the material of building space and learning outcomes are in the low category.